(untitled) (Neo Scientific Peer Reviewed Journal, 2023)
1- Preparing a psychological stress scale for students of the College of Physical Education - University of Baghdad. 2- To identify the level of psychological stress among students of the College of Physical Education - University of Baghdad. The researcher used the descriptive survey method in measuring the psychological stress characteristic of the students of the College of Physical Education, University of Baghdad. He used the scale of (Huda Jalal) for psychological stress after preparing it by applying it to a sample of (120) students from the Faculty of Physical Education (first stage). The data was processed statistically using the statistical bag for social sciences (spss), and the most important conclusions reached by the researcher are: 1- There is a psychological tension among the students of the first stage in the College of Physical Education - University of Baghdad towards performing the skill of the effectiveness of free swimming. 2- Reducing psychological tension had a positive effect on improving the performance of the free swimming activity skill among students of the Faculty of Physical Education. 3- Following the correct methods in learning the skill of free swimming and the visualization and mental recovery procedures had a direct impact on increasing the skillful performance mechanism. In light of the conclusions reached by the researcher, he recommended the following: 1- Benefiting from the measure of psychological tension in measuring the psychological hesitation of other societies in other sports. 2- Conducting a study dealing with the relationship between psychological stress and other psychological variables. 3- The need to develop educational (psychological) curricula to treat some players who suffer from high psychological tensions.